Generasi Z dan Alpha: Adaptasi Teknologi Pendidikan Agama Kristen dalam Meningkatkan Kreativitas dan Inovasi Belajar Siswa: Penelitian - Hulu, Vanbe Toven; Sihombing, Kometa; Siahaan, Rentinawati; aritonang, Titin; Ritonga, Naomi Yolanti Octavia (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Generation Z and Alpha live in the midst of rapid technological developments. This reality demands a new approach in Christian Religious Education to remain relevant and touch the lives of students. This study aims to explore how the adaptation of technology in Christian Religious Education (PAK) learning can increase students' creativity and innovation. The method used is descriptive qualitative through literature studies and observations of technology-based learning in elementary and secondary schools. The results of the study show that the use of digital media such as interactive videos, online learning platforms, and digital Bible applications can increase students' active participation and understanding of Christian values. Thus, the adaptation of technology in PAK is an effective strategy in responding to the challenges of the times and forming a generation that is creative, innovative, and remains rooted in the Christian faith.